Angiostrongylus cantonensis: Epidemiology in the Continental United States and Hawai‘i - Park, Sarah Y (University Clinical, Education & Research Associate (UCERA), 2013)
Autochthonous Angiostrongylus cantonensis infection has been little recognized in the continental United States with the exception of Louisiana. In contrast, it was recognized in Hawai‘i in the early 1960s, and the parasite has been considered endemic since. However, infections were rare until late 2004, when a case cluster was noted on the Island of Hawai‘i. While still uncommon, A. cantonensis infection has continued to emerge throughout the state, especially on the Island of Hawai‘i. Despite increased community awareness, the diagnosis is commonly missed, and the lack of diagnostic tests as well as the challenge of educating clinicians and the public are constant limitations to the prevention and control of this emerging infection.